HISTORY OF CARDIAC AND THORACIC SURGERY The radiologist’s tragedy, or Bland-White-Garland syndrome (BWGS). On the 80th anniversary of the first clinical description of ALCAPA (anomalous left coronary artery from the pulmonary artery) - Mazurak, Magdalena; Kusa, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
In 1933, three doctors from the Massachusetts General Hospital in Boston, Paul Dudley White, William Franklin Bland, and Joseph Garland, described a case of an anomalous origin of the left coronary artery arising from the pulmonary artery (ALCAPA) in a three-month-old boy. The infant died following two weeks of hospitalization. The child’s father was Dr. Aubrey Hampton, a radiologist and colleague of White, Bland, and Garland. The paper presents a perspective view on the occasion of the 80th anniversary of the first clinical description of ALCAPA.